Potential symbiotic effects of date palm seed extract on growth, immunity, antioxidant activities, gut microbiota, expression levels, and Vibrio parahaemolyticus resistance in Shrimp - Mathew, Roshmon Thomas; Alqahtani, Nashi K.; Ghazzawy, Hesham S.; El-Haroun, Ehab; Alkhamis, Yousef Ahmed; Mansour, Abdallah Tageldein; Ganesan, Nagarajan; El Asely, Amel M.; Almutairi, Layla A.; Abdul Kari, Zulhisyam; Eissa, Moaheda E. H.; Eissa, El-Sayed Hemdan (Frontiers in Marine Science, 2025)
Date Palm Seed Extract (DPSE) is known to possess beneficial health-promoting and growth-boosting properties, but its specific influence on whiteleg shrimp (Litopenaeus vannamei) health and physiology has yet to be fully explored. Hence, this study examined how dietary DPSE inclusion impacted growth performance, antioxidant status, immune response, hepatic tissue health, inflammation-related gene expression, and resistance to Vibrio parahaemolyticus in shrimp. The study involved four experimental groups of shrimps that were fed diets with varying DPSE inclusions: 0 (DPSE0), 1 (DPSE1), 2 (DPSE2), and 4 (DPSE4) g/kg diet over a 70-day period. The results indicated that dietary DPSE supplementation led to significantly higher (P<0.05) concentrations of whole-body composition (crude protein, gross energy, and crude lipid) in the treated groups. Conversely, the ash content was significantly reduced (P<0.05) in all DPSE-treated shrimp groups compared to the shrimp fed the control diet. Shrimp-fed DPSE-supplemented diets showed a significantly higher total hemocyte count (THC) compared to the control group (P<0.05). The levels of immunological parameters (phagocytosis, phenoloxidase, and lysozyme) and antioxidant status (superoxide dismutase and catalase) were significantly improved with increasing dietary DPSE levels, indicating a dose-dependent effect (P<0.01). The supplementation of DPSE at 1, 2, and 4 g in shrimp diets significantly improved the mRNA expression of immune-related genes (LGBP, PX, PPA) and antioxidant genes (cytMnSOD, mtMnSOD) compared to the control group (P<0.001). Both total aerobic bacteria and total enteric bacteria were significantly reduced in all DPSE-supplemented groups (P<0.05) compared to the control diet. Dietary inclusion of DPSE improved hepatopancreas tissues and significantly increased resistance to Vibrio parahaemolyticus in shrimp. The results indicate that the dietary inclusion of DPSE can enhance the growth, disease resistance, and overall health of shrimp by regulating immune function, antioxidant status, and immune associated genes regulation. This highlights its potential for sustainable and environmentally beneficial applications in aquaculture.